A Student's Guide to Tropical Marine Biology - Zanga, Haley; Boraski, Audrey; Olendorf, Alana (Open textbook library., 2019)
A Student’s Guide to Tropical Marine Biology is written entirely by students enrolled in the Keene State College Tropical Marine Biology course taught by Dr. Karen Cangialosi.Our goal was to investigate three main aspects of tropical marine biology: understanding the system, identifying problems, and evaluating solutions. Each of the sections contains chapters that utilize openly licensed material and images, and are rich with hyperlinks to other sources. Some of the most pressing tropical marine ecosystem issues are broken up into five sections: Coral Reefs and Diversity, Common Fishes to the Coral Reef, Environmental Threats, Reef Conservation, and Major Marine Phyla. These sections are not mutually exclusive; repetition in some content between chapters is intentional as we expect that users may not read the whole book.